Effectiveness Of Family-Centered Care-Based Supportive Educative Nursing Intervention (SENI) On Increasing Progressive Muscle Mobilization In Stroke Patients At Sembiring Deli Tua General Hospital In 2026 - Meta Rosaulina; MARIA HERMITA MANIK; HELFRINA RAJAGUKGUK (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Stroke is a leading cause of disability and often results in motor function impairment, particularly a decrease in muscle mobilization ability. Stroke patient rehabilitation requires structured nursing interventions and active family involvement. Supportive Educative Nursing Intervention (SENI) based on Family-Centered Care is a nursing approach that emphasizes education, support, and family participation in the recovery process. This study used a quantitative research design with a quasi-experimental approach using a one-group pretest–posttest design. The independent variable was Supportive Educative Nursing Intervention (SENI) based on Family-Centered Care, while the dependent variable was progressive muscle mobilization in stroke patients. The sample consisted of 30 stroke patients undergoing rehabilitation at Sembiring general hospital Deli Tua in 2026 , selected using a purposive sampling technique. Data were collected using a progressive muscle mobilization observation sheet. The intervention was delivered through structured education, family assistance, and progressive muscle mobilization exercises in accordance with standard operating procedures (SOPs). Data were analyzed using univariate and bivariate analysis with the Wilcoxon Signed Rank Test. The results showed an improvement in progressive muscle mobilization ability after the intervention. Statistical analysis revealed a p-value of 0.000 (p < 0.05), indicating a significant effect of Supportive Educative Nursing Intervention based on Family-Centered Care on the improvement of progressive muscle mobilization in stroke patients. In conclusion, Supportive Educative Nursing Intervention (SENI) based on Family-Centered Care is quantitatively effective in improving progressive muscle mobilization in stroke patients and is recommended for implementation in rehabilitative nursing practice.